1985
DOI: 10.1007/bf00002577
|View full text |Cite
|
Sign up to set email alerts
|

The structure of sculpin populations along a stream size gradient

Abstract: SynopsisData on spatial variation of sculpin density, growth and fecundity support the hypothesis that populations of stream fish are structured by changes in risk of predation and prey availability along a gradient in stream size. Cot&s bairdi in warm streams and C. cognate in cold streams exhibit similar patterns. Sculpins in large streams have faster individual growth rates and higher fecundities than those in small streams, but occur at lower density. The patterns appear to be persistent and suggest that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
34
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 37 publications
(49 reference statements)
4
34
0
Order By: Relevance
“…Similar to the Brown and Downhower (1982) and Schmetterling and Adams (2004) with freshwater sculpins, we found the length of Potomac sculpin did not affect movement. Several flood events occurred during our study, and we found, as did Anderson (1985), that floods did not increase movement rates. We hypothesized that the flood effect, if any, would increase downstream movement.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Similar to the Brown and Downhower (1982) and Schmetterling and Adams (2004) with freshwater sculpins, we found the length of Potomac sculpin did not affect movement. Several flood events occurred during our study, and we found, as did Anderson (1985), that floods did not increase movement rates. We hypothesized that the flood effect, if any, would increase downstream movement.…”
Section: Discussionsupporting
confidence: 74%
“…The lack of large potential predators of Potomac sculpin (i.e., salmonids, rock bass Ambloplites rupestris) in Smith Creek may also have affected behavior and movement needs at many scales. The density of Potomac sculpin in our study was considerably higher than would be predicted from other streams with similar widths (Anderson 1985). Anderson (1985) found a consistent relationship between freshwater sculpin density and stream width and hypothesized that a reduction in density with increasing stream width was related to the presence of predators (i.e., salmonids, rock bass) in wider streams.…”
Section: Discussionsupporting
confidence: 65%
“…First, densities of sculpins in the Eel River system were relatively low compared to other streams and rivers. In small streams (3 to 5 meters wide), sculpin densities measured in other studies range from 0.5 to 5 fish m-2 (Anderson 1985, Daniels 1987, Morgan & Ringler 1992. Morgan & Ringler (1992) conducted experimental additions of slimy sculpins, Cottus cognatus, and found that densities of up to 10.1 fish m-2 could be established and maintained.…”
Section: Discussionmentioning
confidence: 97%
“…Differences in habitat choice (Mason & Machidori 1976, Finger 1982, Matheson & Brooks 1982, Daniels 1987, Brown 1991, physiological responses to temperature (Brown 1989), and responses to predation and competition (Andreasson 1972, Finger 1983, Anderson 1985, Brown 1991 have all been suggested as processes promoting segregation. The diet data suggest that neither intranor interspecific predation are very important processes.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies have shown that fish become smaller with progression upstream, because fish size was related to stream depth observed at the habitat unit scale (see, for example, Patrick. 1975;Schlosser, 1982;Anderson, 1985). Hughes (1998) suggested, however, that this relationship does not always apply to drift-feeding stream salmonids.…”
mentioning
confidence: 99%